Burnout and quality of life among masseurs with visual impairment - Polish cross-sectional study. (13th November 2019) - Binder, K; Wrzesińska, M; Tabała, K; Lipert, A; Miller, E
Abstract: Background: Although there are about 1.3 billion people affected by visual impairment (VI), they do not have equal access to social activities, i.e. they are very often unemployed. The authors hypothesized that being job active plays crucial role for their well-being. The aim of the study was to evaluate the level of burnout and quality of life (QoL) among Polish massage therapists with VI and to determine their relationship with sociodemographic and work-related variables. Methods: 43 participants aged 28-63, blind or poor-sighted were surveyed with sociodemographic data questionnaire and Polish versions of the Maslach Burnout Inventory-General Survey to measure burnout and World Health Organization Quality of Life Questionnaire (WHOQOL-BREF) to evaluate quality of life. Results: Low level of burnout was indicated: 6.79 ± 4.45 in the exhaustion, 7.30 ± 3.43 in cynicism and 23.3 ± 5.44 in professional efficacy. Among domains of QoL the psychological one was the highest (73.6 ± 10.0). Professional efficacy correlated with the social QOL domain (ρ = 0.306; t = 2.056; p = 0.046). Among significant socio-demographic determinants of QOL marital status and working conditions were found. The most general explanation is that job activity gives feeling of self-realization, independence and enhance social functioning which has important meaning for QOL and can be a protective factor for burnout among workers with disability (according to researches among healthy professionals they are at high risk of burnout). Conclusions: Job activity is essential for psychosocial rehabilitation in VI. That is why we recommend education tailored to the needs and capabilities of persons with VI to prepare them for work as well as supporting employers in creating jobs opportunities for people with disabilities. Key messages: Job opportunities for people with disabilities mean higher level of psychosocial functioning. Workers with disabilities present lower risk of burnout than professionals without impairment.